Application of Gamification for the Attendance System to Improve Employee Discipline - R. Kaburuan, Kevin, Patria Ludi Permana (International Journal of Advanced Science and Technology, 2020)
The rapid development of technology and information can increase the value and performance of several companies or institutions, one of which is an attendance system that makes it easy to record attendance, absent data recapitulation easier, real time attendance data monitoring and more accurate calculation of working hours. Timeliness of employee attendance is very important to improve discipline so that employees can work with maximum time. But with the Attendance System there are still employees who are late and even more forget to do the fingerprint on the attendance system. So it is necessary to appreciate employees who are disciplined so that they can motivate employees to come before the specified working hours and go home after the specified working hours. For this reason, there is a need to solve the problem in this research, namely the development of gamification in the Attendance System so that the implementation of fingerprints on attendance can run effectively, efficiently and actually, and there is a trophy if it is included in the top 10 accumulation of absences per week / month. It is expected that the development of gamification in the Attendance System can improve employee performance which can be seen from the discipline of entering and leaving work.Keywords: Gamification, Attendance, Technology, Fingerprint